Memória e Amnésia na História da Antropologia - Araújo, Henrique Luís Gomes de (Trabalhos de Antropologia e Etnologia, 2020)
The object of this conference is the semantic difference in the concepts of time in History in general (and in the History of Art, in particular), on the one hand, and in Anthropology on the other. The purpose of this conference is to compare the different meanings in the concepts of time in History (and in Art History in particular), on the one hand, and in Anthropology on the other.